Managing students’ learning interest in civics learning through a genially-based interactive multimedia - Arum, Wahyu Sri Ambar; Khalilah, Hana Naurah; Marini, Arita; Yarmi, Gusti; Safitri, Desy; Dewiyani, Leola (Journal of Education and Learning (EduLearn), 2025)
This study aims to create a Genially based interactive multimedia product to increase interest in learning civics among fifth-grade students. This research and development type uses the analyze, design, develop, implement, and evaluate (ADDIE) model. This study used three samples in the one-to-one stage, six in the small group stage, and 26 in the field test stage. This media produces media quality with a total score percentage of 88%, categorized as very feasible through media expert validation. This product also makes material quality with a total score percentage of 94%, classified as very feasible through content expert validation. The product effectiveness test through the N-Gain test obtained a total score percentage of 1%, which was included in the high category. This study concludes that Genially-based interactive multimedia effectively increases students' interest in civics.